Bank Runs and Moral Hazard : A Review of Deposit Insurance - Anginer, Deniz; Demirguc-Kunt, Asli (World Bank, Washington, DC, 2018)
Deposit insurance is a widely adopted policy to promote financial stability in the banking sector. Deposit insurance helps ensure depositors' confidence in the financial system and prevents contagious bank runs, but it also comes with an unintended consequence of encouraging banks to take on excessive risk. This paper reviews the economic costs and benefits of deposit insurance and highlights the importance of institutions and specific design features for how well deposit insurance schemes work in practice.